2021
DOI: 10.3390/plants10061097
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Cruciferae Glucosinolates in Disease and Pest Resistance

Abstract: With the expansion of the area under Cruciferae vegetable cultivation, and an increase in the incidence of natural threats such as pests and diseases globally, Cruciferae vegetable losses caused by pathogens, insects, and pests are on the rise. As one of the key metabolites produced by Cruciferae vegetables, glucosinolate (GLS) is not only an indicator of their quality but also controls infestation by numerous fungi, bacteria, aphids, and worms. Today, the safe and pollution-free production of vegetables is ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 139 publications
0
37
0
Order By: Relevance
“…Therefore, MIK2 exhibits a unique dual recognition ability by perceiving conserved peptide motifs from endogenous phytocytokines and microbial pathogens. Robust immunity of cruciferous plants against several phytopathogenic fungi, including F. oxysporum , relies on functional glucosinolate biosynthesis ( Humphry et al, 2010 ; Liu et al, 2021 ). Hence, the involvement of SCOOP peptides as potential modulators of glucosinolate biosynthesis to strengthen immunity against fungal pathogens is an additional intriguing aspect for future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MIK2 exhibits a unique dual recognition ability by perceiving conserved peptide motifs from endogenous phytocytokines and microbial pathogens. Robust immunity of cruciferous plants against several phytopathogenic fungi, including F. oxysporum , relies on functional glucosinolate biosynthesis ( Humphry et al, 2010 ; Liu et al, 2021 ). Hence, the involvement of SCOOP peptides as potential modulators of glucosinolate biosynthesis to strengthen immunity against fungal pathogens is an additional intriguing aspect for future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…GSLs represent essential defensive molecules against biotic factors, due to their strong antibacterial and antifungal properties [ 119 , 120 ]. However, to be converted into their active, toxic form (called isothiocyanates), thus performing their biological function, the thioglucose residue of the GSL molecule needs to be removed by the activity of specific ÎČ-thioglucosidases called myrosinases [ 119 ].…”
Section: Plant Metabolism and Lightmentioning
confidence: 99%
“…However, a peak of jasmonic acid (JA), a hormone that is required in plant defence against necrotrophic fungi such as A. brassicicola, is observed in the middle of a light period in Arabidopsis [38]. Lack of a dark period may enhance plant resistance against A. brassicicola and also through extensive production of metabolites with antifungal properties, e.g., phenolic compounds or, characteristic for Brassicas, glucosinolates [39,40]. Glucosinolate biosynthesis is also regulated by light and it has been demonstrated that dark exposure decreases its content in Chinese cabbage seedlings [40,41].…”
Section: Differential Influence Of Day Length On Leaf Morphology and Necrosis Formationmentioning
confidence: 99%